2017
DOI: 10.1002/brb3.747
|View full text |Cite
|
Sign up to set email alerts
|

Effect of food intake on 92 neurological biomarkers in plasma

Abstract: ObjectiveThis study evaluates the effect of food intake on 92 neurological biomarkers in plasma. Moreover, it investigated if any of the biomarkers were correlated with body mass index.Materials and MethodsTwenty‐two healthy subjects (11 male and 11 female aged 25.9 ± 4.2 years) were investigated. A total of 92 biomarkers were measured before a standardized meal as well as 30 and 120 min afterward with the Proseek Multiplex Neurology I kit.ResultsThe levels for 13 biomarkers decreased significantly (p < .001) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 17 publications
1
12
0
Order By: Relevance
“…One other potential limitation of our investigation is the use of non-fasting plasma samples. However, a recent study concluded that timing of food intake only had a modest effect on the levels of the Olink neurology-related biomarkers used in this study 51 . The use of citrate blood collection tubes for the LBCs and EDTA blood collection tubes for INTERVAL is potentially a limitation.…”
Section: Discussionmentioning
confidence: 65%
“…One other potential limitation of our investigation is the use of non-fasting plasma samples. However, a recent study concluded that timing of food intake only had a modest effect on the levels of the Olink neurology-related biomarkers used in this study 51 . The use of citrate blood collection tubes for the LBCs and EDTA blood collection tubes for INTERVAL is potentially a limitation.…”
Section: Discussionmentioning
confidence: 65%
“…It is relevant from a practical point of view to investigate whether these biomarkers are affected by food intake, as the timing of blood sampling in relation to food intake would then be relevant. We have previously reported the effects of food intake on biomarkers analyzed with the Proseek Multiplex CVD III and Proseek Multiplex Neurology I kits (Dencker M et al, 2017a;Dencker M et al, 2017b), and now extend our work with the Proseek Multiplex CVD II kit. The present study, therefore, evaluates the effect of food intake in healthy volunteers on 92 different emerging biomarkers for CVD and inflammation analysed with the Proseek Multiplex CVD II kit.…”
Section: Introductionmentioning
confidence: 52%
“…It is possible to measure multiple plasma proteins simultaneously with for example the Proseek Multiplex CVD II kit and this technology has recently been used in a multitude of studies (Edsfeldt et al, 2016;Goncalves et al, 2015;Gonçalves et al, 2016;Lind et al, 2015a;Lind et al, 2015b;Wiklund et al, 2016;Schiopu et al, 2016), and our investigation adds methodological information to this developing field. We have previously reported the effects of food intake on biomarkers analyzed with the Proseek Multiplex CVD III and Proseek Multiplex Neurology I kits (Dencker M et al, 2017a;Dencker M et al, 2017b), and the findings for those kits were rather different than the Proseek Multiplex CVD II kit. In the Proseek Multiplex CVD III only 17 biomarkers were affected by food intake, and only six biomarkers showed a difference of 10% or more due to food intake (Dencker M et al, 2017b).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The interpretation of both the Proximity Extension Assay and SOMAscan data is heavily dependent on post-data collection processing algorithms and normalization procedures [ 19 , 116 ]. There are several data treatment methods currently developed for transforming PEA and SOMAscan data, each designed to focus on minimizing a specific source of variability.…”
Section: Capture-based Strategiesmentioning
confidence: 99%